The Impact of Zero Carbon Emission Farming on Sustainable Agricultural Development in India: Challenges and Opportunities - Shivam Satyawan Madrewar; Sangeeta Dhinwa; Nimisha Ravindra Khadkikar; Saniya Phiroj Shaikh; Avanti Vivek Bhoite; Shreyash Bhagwan Shinde (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
The agricultural sector in India is at a critical juncture, facing the dual challenges of meeting the growing food demand and addressing the environmental consequences of traditional farming practices. This research paper investigates the impact of zero carbon emission farming as a sustainable alternative to conventional agriculture. Zero carbon emission farming aims to minimize or eliminate carbon emissions through practices such as organic farming, agroforestry, and conservation agriculture. Economically, the adoption of these practices can lead to cost savings for farmers in the long term, although initial investments in green technologies may pose challenges. Socially, the acceptance and implementation of zero carbon farming practices among Indian farmers depend on factors such as awareness, education, and access to resources. This study underscores the need for concerted efforts by the government, private sector, and civil society to support the widespread adoption of zero carbon emission farming. Recommendations include policy incentives, increased investment in research and development, and comprehensive farmer education programs. The paper concludes that while the transition to zero carbon farming presents challenges, it also offers significant opportunities for advancing sustainable agricultural development in India.